Lanna Modernization in Extension Route: Enhancing Creative Tourism Initiatives along the Lampang-Phrae-Uttaradit-Phitsanulok Railway Route in Northern Thailand - Kalaya, Pannathat; Sirithiti, Kanok-orn; Wattapanich, Piya; Thitiyapramote, Natthanan; Mahittipong, Pongvikran; Wattanachet, Pimpisa (Journal of Multidisciplinary in Social Sciences, 2026)
This research aimed to expand and enhance the creative tourism route along the State Railways of Thailand’s northern railway line, specifically extending the previous Chiang Mai-Lampang route to include Phrae, Uttaradit, and Phitsanulok provinces. Through this route expansion, the study focused on improving route configurations and introducing novel products and services aligned with creative tourism objectives. Through a mixed-method approach, the study integrated multiple data collection strategies from a total of 274 individuals: in-depth interviews with 35 key informants, focus group discussions involving 65 participants by purposive selection, meanwhile, the quantitative component, 174 respondents were selected from a finite population of 320 tourists through non-probability quota sampling, with the sample size determined using Krejcie and Morgan’s table. These respondents were all tourists who had purchased commercial railroad travel experiences in 2023. These qualitative and quantitative methodologies, alongside participatory action research principles and field studies, provided comprehensive insights into the development of creative tourism initiatives. Rigorous validation processes ensured the 0.84 reliability test of research instruments. The analysis revealed an extension of the route from a previous study on the Chiang Mai to Lampang railway journey in Northern Thailand, encompassing Lampang, Phrae, Uttaradit, and Phitsanulok Provinces, highlights the historical essence of rail travel and introduces creative tourism activities, fostering a deep connection with the region’s culture. Continuous feedback gathering ensured an audience-centric experience, inspiring curiosity and engagement among travelers. Novel products and services were developed, reflecting the distinct identities of the provinces and reimagining them to align with the region’s cultural landscape. This immersive journey celebrates the area’s rich heritage and diversity. The study’s findings can inform future endeavors in creative tourism development, enhancing travel experiences along the Chiang Mai to Phitsanulok railway journey.